Optimasi Pemupukan pada Pertanian Rempah dengan Algoritme Genetika - Muhammad Fahmi Hidayatullah; Imam Cholissodin; Agus Wahyu Widodo (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Indonesia is an agricultural country which has many agricultural commodities such as spices demanded by foreign countries and has a high trade value. Currently, the production and export of Indonesian spices no longer dominate the global market, Indonesia has lost its glory in the world spices trade. It is caused by many farmers who only use limited experience and knowledge to fertilize the spices which can lead to crop failure and a big loss. Based on these problems, I will design an intelligent system that can optimize the fertilization in agricultural spices so the farmers could get optimal fertilizer for agricultural spices by using Genetic Algorithms. Genetic Algorithms was chosen because this algorithm can be used in problem optimization in a wide search space quickly. Test result using 2 type of plant, 3 types of fertilizers, 100 population size, 700 total generation, 0.3 cr and 0.7 mr combination can meet the nutrient needs of plants. The best result of this system testing can save cost of 0.23%.